Print to fit : the New York Times, Zionism and Israel, 1896-2016 - Auerbach, Jerold S. (Brighton, MA : Academic Studies Press, 2019)
Ever since Adolph Ochs purchased The New York Times in 1896, its enduring masthead motto - ""All The News That's Fit To Print""--Has become news that fits Times' discomfort with the idea, and since 1948 the reality, of a thriving democratic Jewish state in the historic homeland of the Jewish people.
Patriotic loyalty, 1896-1927 -- The Zionist menace, 1928-1939 -- Denial and discomfor, 1933-1948 -- Democratic allies, 1949-1957 -- Conquest and occupation, 1960-1979 -- Arabs and Jews, 1979-1984 -- Moral equivalence, 1984-1988 -- Occupation cruelty, 1988-1989 -- Illusions of peace, 1990-1996 -- Realities of conflict, 1996-2001 -- Blame Israel first, 2002-2006 -- Israeli goliath, 2006-2009 -- Double standards, 2009-2014 -- American loyalty, 2014-2015 -- Epilogue, 2016 -- Afterword.
Series taken from publisher's Web site.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on March 08, 2019).
In English.
eBooks on EBSCOhost
Keywords: New York times; New York times; Arab-Israeli conflict -- Press coverage -- United States; Journalism -- Objectivity -- Uniteted States; Palestine question (1948-); Conflit israélo-arabe -- Couverture de presse -- États-Unis.; LANGUAGE ARTS & DISCIPLINES -- Journalism; SOCIAL SCIENCE / Media Studies; Arab-Israeli conflict -- Press coverage; Journalism -- Objectivity; United States; Adolph Ochs; American Jews; American Journalism; History of Israel; Israel; Middle East policy; NYT:The New York Times; New York Times; Opinion; State of Israel; Times; Zionism; Zionist; anti Zionist; anti semistism in the media; anti semitisim; anti-Zionist.; anti-semitism in the media; anti-semitism.; antisemitism in the media; antisemitism; discrimination; intolerance; journalism; journalist; media; national identity; news and media; news; newspaper history; newspapers; publications; religious intolerance